Establishing an effective clinical data collecting tool for optimal evaluation of native and allograft renal biopsies. Issue 3 (March 2023) - Al Qa'qa', Shifaa'; Al-Fatani, Rehab; Rodriguez-Ramirez, Sonia; Gudsoorkar, Prakash; Geldenhuys, Laurette; Avila-Casado, Carmen
Abstract: Introduction: Percutaneous kidney biopsy is the gold standard method to reach a precise diagnosis in most medical kidney diseases, which positively impacts patient care by personalizing the treatment. Accurate diagnosis in the pathology report for medical kidney diseases requires clinicopathological correlation, and clinical data is not always reachable to the nephropathologist. This study aimed to create a standardized, paperless requisition form compatible with medical renal biopsies. Methods: An initial form was prepared for native and allograft renal biopsies according to the current classification of medical kidney diseases. We invited 33 nephropathologists working in Canadian healthcare institutions to answer survey questions about the need to include a particular aspect of clinical information. According to the responses, we modified the experimental form. Eighty nephrologists were asked to complete a clinical data-collecting form given out as PDF files. The time for completing the form and clinicians' satisfaction were assessed. Results: The experimental form survey was answered by 20 out of 33 nephropathologists (61%) from 14 Canadian healthcare centers. The agreement rate on the questions was from 38.89% to 100.00% (average 83.33% and 77.14% for the native and the allograft section, respectively). Seventeen out of 80 nephrologists and their assistants (21%) responded by completing 22 PDF forms. The time required to finish a PDF form was 10.4 min on average. Nephrologists considered the form time-consuming and suggested making it more clinically relevant. Only seven nephrologists responded to the satisfaction survey; four (57%) were satisfied. Conclusions: Medical information is critical in renal pathology diagnoses. A uniform paperless clinical data requisition form was evolved through an agreement by Canadian nephropathologists.